2021
DOI: 10.2106/jbjs.20.02036
|View full text |Cite
|
Sign up to set email alerts
|

A BMP/Activin A Chimera Induces Posterolateral Spine Fusion in Nonhuman Primates at Lower Concentrations Than BMP-2

Abstract: Background:Supraphysiologic bone morphogenetic protein (BMP)-2 concentrations are required to induce spinal fusion. In this study, a BMP-2/BMP-6/activin A chimera (BV-265), optimized for BMP receptor binding, delivered in a recombinant human collagen:CDHA [calcium-deficient hydroxyapatite] porous composite matrix (CM) or bovine collagen:CDHA granule porous composite matrix (PCM), engineered for optimal BV-265 retention and guided tissue repair, was compared with BMP-2 delivered in a bovine absorbable collagen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 88 publications
(234 reference statements)
1
1
0
Order By: Relevance
“…Our group previously reported that 3 μg/mL rhBMP2 doped nHAp-PEG/PLA presented similar spinal fusion rate and increased bone volume on week 8 comparing to higher dose (10 μg/mL doped nHAp-PEG/PLA) by manual palpation, μCT and histology when applied in vivo to lumbar 4-5 vertebrae rat PLSF model. Our findings were in line with a recent study 14 that evaluated fusion in non-human primates. Our dose window is in line with previous in vitro studies [21][22][23]28,29,31,32 revealing that optimal beneficial osteogenic effect of rhBMP2 takes place within a very tight dose window that would cause no inflammation but osteoinduction when applied to in vivo setting including lumbar spinal fusion model.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our group previously reported that 3 μg/mL rhBMP2 doped nHAp-PEG/PLA presented similar spinal fusion rate and increased bone volume on week 8 comparing to higher dose (10 μg/mL doped nHAp-PEG/PLA) by manual palpation, μCT and histology when applied in vivo to lumbar 4-5 vertebrae rat PLSF model. Our findings were in line with a recent study 14 that evaluated fusion in non-human primates. Our dose window is in line with previous in vitro studies [21][22][23]28,29,31,32 revealing that optimal beneficial osteogenic effect of rhBMP2 takes place within a very tight dose window that would cause no inflammation but osteoinduction when applied to in vivo setting including lumbar spinal fusion model.…”
Section: Discussionsupporting
confidence: 93%
“…Recent research focused on decreasing the dose. 13 A current study 14 delivered BMP2/BMP6/activin A chimera with in a recombinant human collagen plus calcium‐deficient hydroxyapatite porous composite matrix in monkeys for PLSF to overcome problems of supraphysiologic BMP2 concentrations. BMP2 combined with synthetic grafts including polymers, 15 , 16 , 17 bioceramics, 18 , 19 bioactive glass 20 and their composites 21 , 22 , 23 could facilitate adequate PLSF.…”
Section: Introductionmentioning
confidence: 99%